2007
DOI: 10.1194/jlr.m600480-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

The transfer of VLDL-associated phospholipids to activated platelets depends upon cytosolic phospholipase A2 activity

Abstract: We previously reported that VLDL could transfer phospholipids (PLs) to activated platelets. To identify the metabolic pathway involved in this process, the transfer of radiolabeled PLs from VLDL (200 mM PL) to platelets (2 3 10 8

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…Therefore, URB597 exerts anxiolytic-like [159,162], anti-depressant-like [163], and analgesic [164] effects in rodents. On the other hand, methyl-arachidonoyl-fluoro-phosphonate (MAFP), besides being an inhibitor of phospholipase A 2 [165], is also a potent inhibitor of FAAH, showing IC 50 values in the nanomolar range [166]. Comparing the lipophilicity values of URB597 and MAFP (Table 3), it seems clear that these two inhibitors should significantly differ in their affinity for lipid bilayers, and therefore they should have a different preferential access to the active site of FAAH: URB597, much less lipophilic than MAFP (Log P values of 1.04 and 6.63, respectively), should reach the active site of FAAH through the cytosolic port, whereas MAFP should reach it from the membrane port.…”
Section: Structure and Activity Of Endocannabinoids And Related Drugsmentioning
confidence: 99%
“…Therefore, URB597 exerts anxiolytic-like [159,162], anti-depressant-like [163], and analgesic [164] effects in rodents. On the other hand, methyl-arachidonoyl-fluoro-phosphonate (MAFP), besides being an inhibitor of phospholipase A 2 [165], is also a potent inhibitor of FAAH, showing IC 50 values in the nanomolar range [166]. Comparing the lipophilicity values of URB597 and MAFP (Table 3), it seems clear that these two inhibitors should significantly differ in their affinity for lipid bilayers, and therefore they should have a different preferential access to the active site of FAAH: URB597, much less lipophilic than MAFP (Log P values of 1.04 and 6.63, respectively), should reach the active site of FAAH through the cytosolic port, whereas MAFP should reach it from the membrane port.…”
Section: Structure and Activity Of Endocannabinoids And Related Drugsmentioning
confidence: 99%
“…Recently, it has been shown that U73122 forms covalent associations with human PLCβ3, when the phospholipase is associated with mixed micelles [223]. While U73122 has been used as a pan inhibitor of PLC in numerous studies [21,138,[224][225][226][227][228], in the study by Klein et al, instead of inhibiting PLC, U73122 activated human PLCγ1, human PLCβ2 and human PLCβ3, which had been incorporated into micelles to differing magnitudes. Since the PLC used in these studies was in a purified form, it is unclear, how U73122 functions to regulate the extent of PLC activation.…”
Section: Methods To Inhibit Plcmentioning
confidence: 99%